The collision between wireless and biology - Paul Héroux (Heliyon)
This article examines the historical development of the concept of energy of activation, which has been used in the past to frame the belief that non-ionizing electromagnetic radiation is harmless at non-thermal levels.The power and telecommunications industries have used two arguments to support their view that human exposures to non-thermal non-ionizing radiation is inoffensive. First, the radiation is non-ionizing. Second, the energy quanta of the radiation are too weak to overcome the competing energy of thermal motion. Those arguments rest on the Arrhenius equation (1889) and on the concept of energy of activation. Later scientific developments such as the Eyring equation (1935) and the Bennett-Chandler (1977–1978) equation on reaction rates, and the Second Law of Thermodynamics, recognized in living systems by Schrödinger as “negentropy”, all undermine these arguments.The Second Law of Thermodynamics supplies the ionization claimed to be lacking, while some biological processes are independent of thermal motion.We contribute a new view of the physics and biology of non-ionizing electromagnetic radiation hygiene which explains many epidemiological, toxicological and scientific observations.The health effects of non-thermal non-ionizing radiation presently observed are in fact completely supported by physics. Furthermore, the expansion of wireless data rates is in direct conflict with preservation of a healthy environment.